Pengukuran RSSI Jaringan Sensor Nirkabel Berbasis ZigBee pada Berbagai Topologi - Helmy Fitriawan; Roviq Cholifatul Rohman; Herlinawati Herlinawati; Sri Purwiyanti (Jurnal Rekayasa Elektrika, 2020)
In order to get a good performance from a wireless sensor network, it is necessary to measure parameters of the network. RSSI (Received Signal Strength Indicator) is one of the network parameters that measure the signal strength received by a radio receiver in communication module. In this study the RSSI measurement experiment was performed in a wireless sensor network with the ZigBee protocol. Measurements were accomplished in three topologies, i.e. point-to-point, star, and mesh, both indoor and outdoor scenarios. Indoor measurements are carried out within the laboratory with concrete wall partition, while outdoor measurements are carried out in open space with the line-of-sight (LOS) conditions. XCTU software is used to measure RSSI measurements, by sending 100 data packets of 64 bytes with 1 second delivery intervals. Results show that the farther the data transmission distance, the RSSI value relatively decrease due to obstacles and reduced radio signal strength. While, in the mesh topology the addition of a router will also cause a slightly increase in the RSSI value.